Wielcy językoznawcy w Polskiej Akademii Umiejętności .......... 27 - Kowalik, Krystyna; Jarosław Darasz, Wiktor (Autorytety w naszym życiu: Nauka – kultura – media, 2025)
GREAT LINGUISTS AT THE POLISH ACADEMY OF ARTS AND SCIENCESThe article presents the profiles and achievements of selected 23 Polish linguists – members of the Faculty of Philology of the Polish Academy of Sciences, including 5 who currently operate in the structures of PAU, who, thanks to their outstanding scientific achievements, constitute an intellectual elite with unquestionable prestige and authority.